INCIDENCE OF TIBIAL DIAPHYSEAL FRACTURES AMONG PATIENTS PRESENTING WITH MOTORCYCLE ACCIDENTS - Ali, Pervez; Mian Sajjad,; Kashif Mehmood Khan,; Riaz Khoso,; Ejaz Matlo,; Kashif Murtaza,; Dost Muhammad,; Abdul Rasheed,; Zain Zafar,; Nasir Somroo, (Journal of Ayub Medical College Abbottabad, 2022)
Background: To determine the frequency of tibial diaphyseal fractures among patients presenting with motorcycle accidents. It was a cross-Sectional Study, conducted at Department of Orthopaedic Surgery, Jinnah Postgraduate Medical Centre (JPMC), Karachi between May to December, 2020. Methods: All patients irrespective of gender, between ages 18-60 years who suffered from a motorcycle injury with a single bone involvement were eligible for the study. All patients who refused to take part in the study, had head injury, or had multiple fractures were excluded from the study. The data included patient's age, sex, associated bones involved and types of injury. The fractures were classified according to whether it was open or closed. Results: A total of 174 patients were included in the study with a mean±SD age of 43.7±12.4. Tibial diaphyseal fracture was found to be in 111 (63.8%) patients as shown. Duration of fracture, gender, side of fracture, type of fracture was done with respect to Tibial diaphyseal fracture among patients. Insignificant difference was noted in age group (p=0.346), duration of fracture (p=0.087), gender (p=0.672), and type of fracture (p=0.063) whereas significant difference was found in side of fracture (p=0.0001). Conclusion: We highlighted the importance of tibial diaphyseal fractures in middle aged men who use motorcycles as a means of transport in Karachi, Sindh which is a frequent finding among these patients. Efforts should be made at both the community and government levels to increase awareness regarding traffic rules and consequences of reckless driving.